Sustainability in Smart Manufacturing: Trends, Scope, and Challenges - Shah S.; Nautiyal H.; Gugliani G.; Kumar A.; Namboodri T.; Singla Y.K. (My University, 2025)
This text highlights the role of artificial intelligence-powered robots and automation systems in revolutionizing digital manufacturing, covers prod-uct design and customization, and discusses various artificial intelligence algorithms for manufacturing processes and supply chain optimization. It further covers the applications of 3D printing and rapid prototyping for low-carbon development. Features: • Discusses microwave hybrid heating based on innovative joining tech-niques, applications of 3D printing, and rapid prototyping for low carbon development • Explains the role of artificial intelligence in digital manufacturing, data security, privacy issues, and defense mechanism • Provides an overview of artificial intelligence-powered robots and automation systems for revolutionizing digital manufacturing, and techniques for soft robotic structures • Presents case studies related to Six Sigma, digital manufacturing, and supply chain manufacturing • Explains artificial intelligence and machine learning-based high-predicted models for accurate data analysis in industry automation It is primarily written for senior undergraduate, graduate students, and academic researchers in the fields of manufacturing engineering, industrial engineering, production engineering, mechanical engineering, and aerospace engineering. © 2024 selection and editorial matter, Saumya Shah, Hemant Nautiyal, Gaurav Gugliani, Ashwani Kumar, Tanuj Namboodri and Yogesh Kumar Singla; individual chapters, the contributors.